Volume 4A: Combustion, Fuels and Emissions 2017
DOI: 10.1115/gt2017-63041
|View full text |Cite
|
Sign up to set email alerts
|

Time-Response of Recent Prefilming Airblast Atomization Models in an Oscillating Air Flow Field

Abstract: The present study investigates the response of recent primary breakup models in the presence of an oscillating air flow, and compares them to an experiment realized by Müller and coworkers in 2008. The experiment showed that the oscillating flow field has a significant influence on the Sauter Mean Diameter (SMD) up to a given frequency. This observation highlights the low-pass filter character of the prefilming airblast atomization phenomenon, which also introduces a significant phase shift on the dynamics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Hence, the discrepancy comes from the calibration constants. This model was already compared to an experiment similar to the present one in a previous publication (Chaussonnet et al 2017) and it was also found to deliver too small droplets. This is because in the bimodal PDF used by this model, one peak is overestimated compared to the other.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…Hence, the discrepancy comes from the calibration constants. This model was already compared to an experiment similar to the present one in a previous publication (Chaussonnet et al 2017) and it was also found to deliver too small droplets. This is because in the bimodal PDF used by this model, one peak is overestimated compared to the other.…”
Section: Discussionmentioning
confidence: 60%
“…This is because in the bimodal PDF used by this model, one peak is overestimated compared to the other. After recalibration, it delivered a good prediction of the SMD (Chaussonnet et al 2017). For all correlations, the dependency on the ambient pressure is represented by the gas density, whose exponent is given in Table 8.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations